(untitled) - Ohmae, Kenichi (New York, 1985)
In a world where the growing parity among American multinationals and their European and Japanese counterparts has made technological and marketing advantages increasingly difficult to acquire or sustain, Triad Power offers a pragmatic alternative cross-cultural alliances that accept a future in which change is inevitable, and where only risks bring rewards. Required reading for senior and general managers and for corporate planners and financial analysts, it is a challenging, thought-provoking, cosmopolitan look at the new rules of global competition
Keywords: Joint ventures,International business enterprises,Competition, international,Doanh nghiệp kinh doanh quốc tế,Cạnh tranh, quốc tế,Liên doanh